2011
DOI: 10.1097/qad.0b013e3283455dff
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of poor locomotor performance in HIV-infected patients

Abstract: One of two adults with controlled HIV infection had poor lower limb muscle performance, which might put this population at risk of falls and fracture. The 5STS test is a simple test that should be recommended to assess muscular performance in HIV care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 37 publications
7
91
1
1
Order By: Relevance
“…The characteristics of our population differed from those of Richert et al [5]. Our sample was predominantly female (67.53%) and the median age was 45.4 years, whereas the Bordeaux team studied a group consisting of 80% men with a median age of 47.6 years (IQR=41.8-53.9) [5,13,14]. Most studies show that the prevalence of these disorders is directly related to age [2,9,10].…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…The characteristics of our population differed from those of Richert et al [5]. Our sample was predominantly female (67.53%) and the median age was 45.4 years, whereas the Bordeaux team studied a group consisting of 80% men with a median age of 47.6 years (IQR=41.8-53.9) [5,13,14]. Most studies show that the prevalence of these disorders is directly related to age [2,9,10].…”
Section: Discussioncontrasting
confidence: 45%
“…Pathological results were found for 28.9% of patients in the "timed up and go" test, 9.7% in the "fivetime sit-to-stand" test and 4.9% in the speed of walking 4 m test. In the study made by Richert et al [5], the test with most frequent alterations was the "five-time sit-to-stand" (53.3%), followed by the "timed up and go" test (10.5%) and standing on one leg with the eyes closed (9.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the results highlight the importance of a HIV uninfected comparison group when investigating non-HIV related outcomes. Several recent functional performance studies, showed reduced 6-MW distance [10,13,19] or LCDW time [14] in HIV-infected adults using normative data. In this study we found no significant difference in the 6-MW distance between HIV-infected on successful ART and uninfected men with similar age-related comorbidity, even with adjustment for BMI.…”
Section: Resultsmentioning
confidence: 99%
“…Richert et al recently reported poor performance in the six-minute walk (6-MW) in a quarter of 324 HIV-infected adults (median age 48 years) based on normative data, generated by Enright's reference equation using age, sex, weight, and height [10]. Esposito and colleagues found the 6-MW distance to be 5% lower than expected in 27 younger men [11] using the same reference equation [12].…”
Section: Introductionmentioning
confidence: 99%